STUDI TENTANG KAFA’AH DALAM PERKAWINAN PERSPEKTIF MAQASHID SYARIAH DAN HUKUM POSITIF - M. Khoirul Muzakki; Muhammad al-Muizzul Hafidz (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2024)
Kafa’ah is the principle of compatibility or equality in marriage that is widely discussed in classical Islamic jurisprudential literature. It encompasses aspects such as religion, lineage, economic status, profession, and honor. This concept aims to maintain the welfare and stability of the household. Although kafa’ah is not included among the pillars or legal requirements of a valid marriage under Islamic law, in social practice—particularly within traditional Indonesian society—considerations of kafa’ah are still applied, often serving as grounds for rejecting a marriage due to differences in social status or family background. However, rapid social change has encouraged a shift in the meaning of kafa’ah, especially among younger generations and urban communities. This study employs a qualitative normative approach using a literature review method. Data were obtained from classical fiqh texts of the four Islamic schools of law, statutory regulations such as Law Number 1 of 1974 and the Compilation of Islamic Law, as well as secondary sources including academic journals and social surveys. Data analysis was conducted using descriptive-analytical and contextual techniques with a maqāṣid al-sharī‘ah approach. The findings indicate that although kafa’ah does not have formal legal force within national law, the concept continues to exist within societal culture. The relevance of kafa’ah in the modern era lies in its substantive values that support the objectives of marriage, such as a shared vision of life, religious commitment, and moral character. Therefore, kafa’ah should be understood as a dynamic concept that can be contextually reinterpreted to create families that are peaceful, loving, and compassionate.